A Survey on Online Political Participation, Social Capital, and Well-Being in Social Media Users—Based on the Second Phase of the Third (2019) TCS Taiwan Communication Survey Database - Zhong, Fangqi; Li, Pengpeng; Xi, Jinchao (Frontiers in Psychology, 2022)
This study focused on the frequency of social media use. Through investigating and verifying the correlations between social media use frequency, online political participation, and social capital, we derived two models of socialization that affect citizen well-being and, accordingly, proposed strategic suggestions for democratic society construction and network management. This study drew upon the 2019 Taiwan Communication Survey database and used structural equation modeling (SEM) as a statistical method to explore the causal relationship between these four variables (social media use, online political participation, social capital and well-being). The data analysis yielded an overall good fit with the overall fit indicators: χ2 = 214.417, df = 84, p = 2.293, RMSEA = .028, GFI = .998, CFI = .986, SRMR = .066, and CN = 993.411. Future communication scholars who wish to explore issues related to new media users can draw on this model for subsequent research.